2208. Rates of Medically-Attended RSV among US Adults: A Systematic Review and Meta-Analysis. (15th December 2022) - McLaughlin, John M; Khan, Farid L; Begier, Elizabeth; Swerdlow, David; Jodar, Luis; Falsey, Ann R
Abstract: Background: Adult respiratory syncytial virus (RSV) vaccines are in late stages of development. A comprehensive synthesis of adult RSV burden is needed to inform public health decision-making. Methods: We performed a systematic review and meta-analysis of studies describing the incidence of medically-attended RSV (MA-RSV) among US adults. We also identified studies reporting nasopharyngeal (NP) or nasal swab RT-PCR results with paired serology (four-fold-rise) or sputum (RT-PCR) to calculate RSV detection ratios quantifying improved diagnostic yield after adding a second specimen type ( ie, serology or sputum). Results: We identified 14 studies with 15 unique MA-RSV incidence estimates, all based on NP or nasal swab RT-PCR testing alone. Pooled annual RSV-associated incidence per 100, 000 adults ≥65 years of age was 178 (95%CI: 152‒204; n=8 estimates) hospitalizations (4 prospective studies: 189; 4 model-based studies: 157), 133 (95%CI: 0‒319, n=2) emergency department (ED) admissions, and 1519 (95%CI: 1109‒1929, n=3) outpatient visits. Based on 6 studies, RSV detection was ∼1.5 times higher when adding paired serology or sputum. After adjustment for this increased yield, annual RSV-associated rates per 100, 000 adults ≥65 years were 267 hospitalizations (UI: 228‒306) (prospective: 282; model-based: 236), 200 ED admissions (UI: 0‒478), and 2278 outpatient visits (UI: 1663‒2893). Persons < 65 years with chronic medical conditions were 1.2−28 times more likely to be hospitalized for RSV depending on risk condition. Conclusion: The true burden of RSV has been underestimated and is significant among older adults and individuals with chronic medical conditions. A highly effective adult RSV vaccine would have substantial public-health impact. Disclosures: John M. McLaughlin, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Farid L. Khan, MPH, Pfizer: Employee|Pfizer: Stocks/Bonds Elizabeth Begier, M.D., M.P.H., Pfizer: Employee|Pfizer: Stocks/Bonds David Swerdlow, MD, Pfizer: Advisor/Consultant|Pfizer: Stocks/Bonds Luis Jodar, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Ann R. Falsey, MD, BioFire Diagnostics: Grant/Research Support|Janssen: Grant/Research Support|Merck, Sharp and Dohme: Grant/Research Support|Novavax: Advisor/Consultant|Pfizer: Grant/Research Support.